Economic Diplomacy and the Origins of the Second World War : Germany, Britain, France, and Eastern Europe, 1930-1939 - Kaiser, David E., 1947- (Book collections on Project MUSE., 1980)
Although the political and military aspects of great-power diplomacy in Eastern Europe during the interwar period have been studied extensively, the economic aspects have been relatively neglected. Drawing on documentary material that has only recently been made available, David Kaiser redresses the balance in his discussion of the expansion of German trade with Eastern Europe during the 1930s and the British and French failure to respond to it. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.